Perencanaan Kanban Card Controller (KCC) dalam Pengendalian Tingkat Produksi Guna Meminimalisasi Kekurangan dan Kelebihan Produksi - Annisa Kesy Garside (Department Industrial Engineering, University of Muhammadiyah Malang, 2000)
This research has aim to plan Kanban Control Card (KCC) in production rate controlling some products as: Office Table (MTK), Tower Chest Four Flours (TC-4),Tower Chest Six Flours (TC-6), Simple Table (MD).In this research we need data such as : production demand data history, production lead time, demand forecasting and production data base from demand history ( 25 weekly periodic), then forecast demand in periodic 26 tli using Time series method with Trend Analysis in a second periodic.Using MRP logic, forecasting result account to result Planed Order Release (PORs) for each work station. From the data analysis can be found : the number ofKanban Card in each work station of production devision and the second is less maximum inventory value than inventory value using MRP, so TIT is proved not efective in a fluctuative production rate.